Immersive visualization of movement in patients with hemophilic ankle arthropathy. Multicenter, single-blind, randomized clinical trial - Roberto Ucero-Lozano; Raúl Pérez-Llanes; Rubén Cuesta-Barriuso; Elena Donoso-Úbeda (Medical Journals Sweden, 2024)
Objective: To evaluate the efficacy of immersive movement observation in adult patients with haemophilic ankle arthropathy. Design: Multicentre, single-blind, randomized clinical trial. Subjects: 48 patients with haemophilia. Methods: Patients were randomly allocated to 2 groups (180º immersive video-based visualization of movement and a control group with no intervention). Twenty-eight consecutive 15-min home sessions, 1 per day, of immersive visualization of ankle flexion-extension movement were carried out. Three evaluations were performed: pretreatment (T0), post-intervention (T1), and at 16 weeks' follow-up (T2). The primary variable was joint-pain intensity (visual analogue scale). The secondary variables were conditioned pain modulation (Conditioned Pain Modulation Index), pressure pain threshold (pressure algometer), range of motion (goniometry) and kinesiophobia (Tampa Scale of Kinesiophophia). Results: There were intergroup differences in pain intensity (F = 37.14; p < 0.001), conditioned pain modulation (F = 5.40; p = 0.006), and dorsal (F = 19.17; p < 0.001) and plantar (F = 9.27; p<0.001) ankle flexion. More than 50% of experimental group patients exhibited changes exceeding the minimum detectable change in pain intensity (MDC = 0.43), and the pressure pain threshold in the extensor carpi radialis longus muscle (MDC = 1.34) and malleolus (MDC = 4.93). Conclusions: 180º immersive video-based visualization of movement can improve the intensity of pain, conditioned pain modulation, and ankle range of motion in patients with haemophilic ankle arthropathy.